Kualitas Air Sumur Dekat SPBU Rendani Kelurahan Wosi Kecamatan Manokwari Barat Kabupaten Manokwari Provinsi Papua Barat - David Victor Mamengko; Syafrudin Raharjo; Pribowo Angling Kusumo; Agnes Dyah Novitasari Lestari (FMIPA Universitas Papua, 2023)
Wells are a groundwater source that is widely used by Indonesian citizens for sanitation and hygiene purposes. Well water quality is influenced by internal factors, namely the condition of the well itself, and external factors, namely the environment around the well. This research aims to analyze the quality of well water near the Rendani gas station, Wosi Village, West Manokwari District, Manokwari Regency, West Papua Province and compare it with the necessary water quality standards. In Indonesia, to guarantee the suitability of well water, water quality standards are stipulated in the Regulation of the Minister of Health Republic of Indonesia No. 32 of 2017. The research results show that the TDS, temperature, turbidity, sulfate, nitrate, iron, manganese and pH parameters meet the quality standards, while the chemical parameters nitrite, chromium (VI) and total coliform do not meet the quality standards. Therefore, it is necessary to treat the water to reduce levels of nitrite, chromium (VI) and total coliform before well water is consumed by residents.